2019
DOI: 10.1016/j.mcn.2019.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Norepinephrine control of ventromedial hypothalamic nucleus glucoregulatory neurotransmitter expression in the female rat: Role of monocarboxylate transporter function

Abstract: The ventromedial hypothalamic nucleus (VMN) is a critical component of the neural circuitry that regulates glucostasis. Astrocyte glycogen is a vital reserve of glucose and its oxidizable metabolite L-lactate. In hypoglycemic female rats, estradiol-dependent augmentation of VMN glycogen phosphorylase (GP) protein requires hindbrain catecholamine input. The research here investigated the premise that norepinephrine (NE) regulation of VMN astrocyte metabolism shapes local glucoregulatory neurotransmitter signali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 54 publications
2
20
0
Order By: Relevance
“…As NO neurons contain ER proteins (Uddin et al, 2019), intrinsic ER likely mediate estradiol stimulation of nNOS expression. Results affirm prior reports that in female rats, site-specific targeting of exogenous NE to the VMN elicits concomitant down-versus upregulation of glucostimulatory (nNOS) and glucoinhibitory (GAD) signaling marker proteins, which infers that VMN neuroenergetic stability is enhanced by NE (Mahmood et al, 2019). This assumption remains unverified as methodology to support analysis of single-nerve cell ATP content is currently unavailable; thus, definitive evidence that glucoregulatory transmitter responses to NE reflect a positive shift in energy state is yet to be attained.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…As NO neurons contain ER proteins (Uddin et al, 2019), intrinsic ER likely mediate estradiol stimulation of nNOS expression. Results affirm prior reports that in female rats, site-specific targeting of exogenous NE to the VMN elicits concomitant down-versus upregulation of glucostimulatory (nNOS) and glucoinhibitory (GAD) signaling marker proteins, which infers that VMN neuroenergetic stability is enhanced by NE (Mahmood et al, 2019). This assumption remains unverified as methodology to support analysis of single-nerve cell ATP content is currently unavailable; thus, definitive evidence that glucoregulatory transmitter responses to NE reflect a positive shift in energy state is yet to be attained.…”
Section: Discussionsupporting
confidence: 88%
“…Present data show that þ2 hr after intra-VMN NE administration, plasma glucose levels were measurable within the normal range, while circulating corticosterone and FFA concentrations were elevated. Previous observations of NE-associated mild hypoglycemia and unmodified FFA values at 1 hr posttreatment indicate that these specific responses adhere to distinctive temporal patterns, whereas hypercorticosteronemia is a uniform reaction, at least up to 2 hr posttreatment (Mahmood et al, 2019). Earlier studies showed that pharmacological inhibition of VMN GP activity by 1,4-dideoxy-1,4-imino-D-arabinitol did not alter euglycemic patterns of corticosterone secretion but prevented hypoglycemic hypercorticosteronemia (Alhamami et al, 2018).…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations